2022
DOI: 10.51459/futajeet.2022.16.1.420
|View full text |Cite
|
Sign up to set email alerts
|

Strength Evaluation of Pozzolanic Concrete Containing Calcined Ceramic Waste and Glass Waste Powder

Abstract: The problems associated with the production of cement used for concrete such as emission of toxic gases, high energy demand, and natural resources consumption, constitute adverse effects on ecology and the economy. However, the use of construction and demolition wastes such as ceramic tiles and glass waste as a partial replacement for cement will help in mitigating the aforementioned problems. Therefore, this study presents the results of an experimental investigation on the strength property of concrete made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Based on the proximity of silicate and alumina compositions obtained showed that kaolin used has silicate and aluminate levels near other kaolin utilized by other researchers such as Faluyi et al, [3], Dewi et al, [13], Arum et al, [18], although there are still many other materials such as K2O, Fe2O3, TiO2, MgO, SO3 etcetera in lesser contents. These compositions are in agreement with the result of FTIR, which shows that the chief elements of the functional group for the binders are alumunium, silicon and iron.…”
Section: Outcome Of Durability Testmentioning
confidence: 81%
See 1 more Smart Citation
“…Based on the proximity of silicate and alumina compositions obtained showed that kaolin used has silicate and aluminate levels near other kaolin utilized by other researchers such as Faluyi et al, [3], Dewi et al, [13], Arum et al, [18], although there are still many other materials such as K2O, Fe2O3, TiO2, MgO, SO3 etcetera in lesser contents. These compositions are in agreement with the result of FTIR, which shows that the chief elements of the functional group for the binders are alumunium, silicon and iron.…”
Section: Outcome Of Durability Testmentioning
confidence: 81%
“…Past research on geopolymer had centered on the use of alkali-activated fly ash and slag as binder [3,16,17,18], investigation of non-calcined natural kaolin as partial replacement of cement [19,20,21,22]. Also, study on development of geopolymer concrete using ground granulated blast furnace slag [23,24,25] and palm oil fuel ash-fly ash [26,27,28,29,30,31,32].…”
Section: Introductionmentioning
confidence: 99%